2013
DOI: 10.1136/bmj.f2032
|View full text |Cite|
|
Sign up to set email alerts
|

Genital warts in young Australians five years into national human papillomavirus vaccination programme: national surveillance data

Abstract: Objective To measure the effect on genital warts of the national human papillomavirus vaccination programme in Australia, which started in mid-2007.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
278
1
11

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(317 citation statements)
references
References 16 publications
11
278
1
11
Order By: Relevance
“…6 Data from Australia, the United States and the United Kingdom have shown that the vaccine is effective, with population level reductions in rates of genital warts, HPV and cervical cancer lesions. [7][8][9][10] Recent data from a populationbased study in the US, where HPV vaccine uptake has been <40%, found a reduction in HPV vaccine-type prevalence from 11.5% to 5.1% pre-and post-vaccine, respectively. 11 In Canada, between 2007 and 2009 all provinces and territories launched school-based HPV vaccine programs.…”
mentioning
confidence: 99%
“…6 Data from Australia, the United States and the United Kingdom have shown that the vaccine is effective, with population level reductions in rates of genital warts, HPV and cervical cancer lesions. [7][8][9][10] Recent data from a populationbased study in the US, where HPV vaccine uptake has been <40%, found a reduction in HPV vaccine-type prevalence from 11.5% to 5.1% pre-and post-vaccine, respectively. 11 In Canada, between 2007 and 2009 all provinces and territories launched school-based HPV vaccine programs.…”
mentioning
confidence: 99%
“…12 Targeted vaccination of MSM has been shown to be cost-effective up to and beyond the age of 26 years. 13,14,15 Emerging evidence suggests that HPV-4v may provide additional benefits in older sexually experienced MSM who have previous exposure to HPV by reducing high grade anal lesions (HGAIN) progression and recurrence among MSM.…”
Section: Introductionmentioning
confidence: 99%
“…24 Our observed safety findings are also similar to that of other studies, whereby vaccine recipients have higher rates of injection site pain, erythema and swelling, but similar rates of systemic AEs. 32 Given the high vaccine efficacy seen in the clinical trials, and the fact that in the 8 y since its original licensure, the qHPV vaccine has been shown to be highly effective at the population level, with marked reductions in the prevalence of HPV vaccine-type related infection and disease in many countries, [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] our findings suggest the vaccine should be equally effective in sub-Saharan African women.…”
mentioning
confidence: 99%